WAVE FRONTS OF ULTRADISTRIBUTIONS VIA FOURIER SERIES COEFFICIENTS - Dolićanin-Djekić, Dijana; Maksimović, Snjezana; Sokoloski, Petar (Matematichki Bilten, 2015)
We shall use the properties of the product of periodic ultradistributions and give a new description of the wave front of an ultradistribution \(fD^′ *(R^d)\) in terms of Fourier series coefficients.